A Review: Image enhancement approaches using Histogram Equalization (International Journal of Engineering and Computer Science, 2015)
Image enhancement is to process the image for getting more suitable result than original image for specific parameters. Many images suffer from poor contrast. Image enhancement improves an image appearance by increasing dominance of some features between different regions of image. Histogram equalization (HE) is that which is widely used for enhancing contrast in various parameters due to its simple function. In this paper various enhancement techniques in literature are discussed with their effects and methodologies